Faktor Penyebab Keterlambatan Waktu Pengembalian Berkas Rekam Medis Pasien Rawat Inap - Faizah Wardhina; Nina Rahmadiliyani (Politeknik Negeri Jember, 2022)
The activity of returning medical record files for inpatients at Mawar Hospital has a standard return time of 1 x 24 hours after the patient returns. Medical records that experience delays in returning will have an impact on the delay in data processing, delays in submitting insurance claims, and delays in service to patients. The purpose of this research was to determine the factors causing the delay in returning inpatient medical record files at Mawar Hospital. The research method used is qualitative. The research subjects were the head nurse of the inpatient room and the head of the medical record, also called the main informant. In this study, the validity of the data was also carried out by triangulation to other informants, an inpatient nurse. The conclusions of this study are the factors that cause delays in returning the medical record files of inpatients at Mawar Hospital: man factor are doctors or nurses, the material factor is an incomplete filling of medical record files, the method factor is incomplete standard operating procedures, the money factor is no budget for granting rewards for doctors or nurses in carrying out their duties.